2019
DOI: 10.1136/gutjnl-2019-318532
|View full text |Cite
|
Sign up to set email alerts
|

A novel faecalLachnoclostridiummarker for the non-invasive diagnosis of colorectal adenoma and cancer

Abstract: ObjectiveThere is a need for early detection of colorectal cancer (CRC) at precancerous-stage adenoma. Here, we identified novel faecal bacterial markers for diagnosing adenoma.DesignThis study included 1012 subjects (274 CRC, 353 adenoma and 385 controls) from two independent Asian groups. Candidate markers were identified by metagenomics and validated by targeted quantitative PCR.ResultsMetagenomic analysis identified ‘m3’ from a Lachnoclostridium sp., Fusobacterium nucleatum (Fn) and Clostridium hathewayi (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
221
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(234 citation statements)
references
References 38 publications
8
221
1
4
Order By: Relevance
“…Paraclostridium strain CR4 was isolated from sugar cane bagasse involved in hydrogen and butyric acid production [52]. Other genera were found in and were isolated from human intestine microbiome [53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paraclostridium strain CR4 was isolated from sugar cane bagasse involved in hydrogen and butyric acid production [52]. Other genera were found in and were isolated from human intestine microbiome [53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, studies on the microbiomes from the patients with autism spectrum disorder revealed an increased number of Terrisporobacter, Lachnoclostridium [55]. Lachnoclostridium was identi ed as a novel bacterial marker for the non-invasive diagnosis of colorectal adenoma [56]. It was also found that most of the gut butyrate-producing bacteria were signi cantly decreased in patients with non-small-cell lung cancer compared to healthy adults [57].…”
Section: Discussionmentioning
confidence: 99%
“…For the qPCR method, the abundance (A) of P. micra in a sample was calculated as the ΔCq relative to the total bacterial DNA in the sample, and the relative abundance was calculated as ln (A × 10 9 +1). For 16S rRNA sequencing data, the A of an OTU in a sample was calculated as the ratio of the sequence count of the OTU relative to the total number of sequences in the sample, and the relative abundance of the OTU was determined as ln (A × 10 6 +1) ( 38 ). Differentially abundant OTUs were selected with the Wilcoxon rank-sum test for the comparison of healthy subjects with the CRC or CRA group ( 39 ).…”
Section: Methodsmentioning
confidence: 99%
“…The use of F. nucleatum together with FIT may improve the detection accuracy for advanced colorectal neoplasia [79]. A most recent report indicated that the combination of F. nucleatum, Clostridium hathewayi, Lachnoclostridium sp., Bacteroides clarus, and FIT presented a high detection accuracy, with a specificity of 81.2% and sensitivity of 93.8% [80].…”
Section: Faecal-based Microbe Detectionmentioning
confidence: 95%